Pemanfaatan AI dan Game Edukatif sebagai Inovasi Pembelajaran di SDN 1 Sumber Agung: Pengabdian - Riswandi; Muhammad Nurwahidin; Agus Salim; Akmal Nur; Nursya Fathin Nadiya (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service program aims to enhance the competence of teachers at SDN 1 Sumber Agung in utilizing Artificial Intelligence (AI) and educational games as innovative learning tools. The program was conducted through workshops, mentoring sessions, and hands-on practice using various AI platforms and simple educational game development aligned with classroom content. Evaluation using a Likert-scale questionnaire indicates that teachers responded positively in several aspects, including understanding the material, ease of technology use, ability to apply AI media and educational games, and increased creativity in designing learning activities. The results demonstrate that the training effectively strengthened teachers’ technological, pedagogical, and content knowledge (TPACK) in an integrated manner. The program also increased teachers’ enthusiasm for adopting digital innovations and broadened the variety of learning strategies used in the classroom. Overall, this program successfully supported a shift toward more interactive, engaging, and student-centered learning practices.